Korean- English Code Mixing and Code Switching Of New Jeans’s Song - Margaretta, Witness Eunike; Rangkuti, Rahmadsyah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
This paper reviewed code-mixing and code-switching along with the worldwide recognition of K-Pop songs by analyzing the English usage of